An Overview Of The Bauxite Supply/Demand Position For Australia - George C. Reynolds (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
INTRODUCTION The overall importance of the minerals industry during the next 20 years was highlighted In "The Global 200 Report to the President" (Barney, 1982) in the following terms: "The industrial and agricultural processes that are taken for granted today would be severely disrupted of any one of dozens of critical minerals ceased to be available in dependable, reasonably priced supply. Supply in turn has become highly energy intensive and international In scope ...... because resources are not uniformly distributed geographically, political considerations (also) become an Important determinant of price and trade patterns." In attempting to determine Australia’s contribution of bauxite raw materials to the world of the future, this paper necessarily also concerns itself with the alumina and aluminium industry to which it supplles the raw material. It is an industry which is energy intensive, International in scope and heavily influenced by political considerations. The aluminium industry has shown a remarkably rapid growth during the past 20 years (Fig. 1).